2020
DOI: 10.1111/bph.15165
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional opioid receptor agonism and antagonism by a novel macrocyclic tetrapeptide prevents reinstatement of morphine‐seeking behaviour

Abstract: Background and Purpose: The macrocyclic tetrapeptide natural product CJ-15,208 (cyclo[Phe-D-Pro-Phe-Trp]) is a multifunctional μ-opioid receptor and κ-opioid receptor agonist and κ-opioid receptor antagonist that produces antinociception and prevents stress-induced reinstatement of extinguished cocaine-conditioned place preference (CPP). We hypothesized that an analogue of CJ-15,208, cyclo[Pro-Sar-Phe-D-Phe], would demonstrate multifunctional μ-opioid receptor and κ-opioid receptor ligand activity, producing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 51 publications
(91 reference statements)
3
27
0
Order By: Relevance
“…Mice place conditioned with either isomer demonstrated no significant preference or aversion for their respective drug-paired chamber. These results are consistent with earlier tests of multifunctional macrocyclic tetrapeptides [ 9 , 19 ] and could reflect the counteracting effects of agonism at multiple opioid receptors such as MOR and KOR [ 9 , 10 ]. In contrast to 5 , isomer 3 did not demonstrate significant MOR-mediated agonism, but rather KOR- and DOR-mediated antinociception.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Mice place conditioned with either isomer demonstrated no significant preference or aversion for their respective drug-paired chamber. These results are consistent with earlier tests of multifunctional macrocyclic tetrapeptides [ 9 , 19 ] and could reflect the counteracting effects of agonism at multiple opioid receptors such as MOR and KOR [ 9 , 10 ]. In contrast to 5 , isomer 3 did not demonstrate significant MOR-mediated agonism, but rather KOR- and DOR-mediated antinociception.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of significant decreases in respiratory rates for all three CJ-15,208 isomers was very promising. We have previously shown that the multifunctional macrocyclic tetrapeptide cyclo [Pro-Sar-Phe- d -Phe] exhibits reduced liabilities, particularly respiratory effects, and that the peptide’s KOR agonist activity appears to offset respiratory depression mediated by MOR [ 9 ]. In contrast, treatment with [ d -Trp]CJ-15,208 isomers 4 and 5 decreased respiratory rates; this effect of 4 was surprising, given the lack of MOR agonist activity by this isomer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations